Studi Komparatif Hukum Perjudian dalam Perspektif Sosial-Budaya dan Legalitas Indonesia dan Thailand - Aura Eka Rahayu; Nurhilmiyah (CV Rewang Rencang, 2025)
The purpose of this study is to analyze gambling from the perspective of Indonesian and Thai law. From the perspective of Indonesian criminal law, the crime of gambling is threatened by the laws and regulations in force in Indonesia, namely Law Number 7 of 1974 concerning the Control of Gambling, Article 303 of the Criminal Code, Article 303 bis of the Criminal Code and Government Regulation Number 9 of 1981 concerning the Implementation of Gambling Control. Meanwhile, Thailand legalizes gambling by dividing it into two categories that have been stated in a regulation, namely the Thai Civil and Commercial Code B.E. 2466 (1923) or the Civil and Commercial Code B.E. 2466, Gambling Act, B.E. 2478 (1935) or the Gambling Law B.E. 2478 and the Government Lottery Office Act B.E. 2517 (1974) or the Government Lottery Office Law B.E. 2517 which regulates gambling currently in Thailand. Articles 835 – 855 of the Civil and Commercial Code. This research is a normative legal research with a comparative approach, using library research data collection tools as data collection techniques and analyzed using qualitative methods.